Synthesis and antiproteasomal activity of novel O-benzyl salicylamide-based inhibitors built from leucine and phenylalanine - Jorda, Radek; Dušek, Jan; Řezníčková, Eva; Pauk, Karel; Magar, Pratibha P; Imramovský, Aleš; Kryštof, Vladimír (European journal of medicinal chemistry, 2017)
Inhibition of protein degradation is one of strategies for suppression of uncontrolled proliferation of cancer cells. Proteolytic degradation in cells is mainly ensured by proteasome and its inhibition by bortezomib showed benefit in clinical use for the treatment of multiple myeloma. We report here the library of antiproteasomal O-benzyl salicylamides built from leucine and phenylalanine. Prepared compounds displayed antiproliferative activity on K562, CEM and U266 cancer cell lines, ranging from high micromolar to submicromolar GI50 values. The most potent compounds (series 4 and 6) were further assayed for their inhibition of chymotrypsin-like protease activity of the 26S proteasome in U266 cells. The majority of compounds inhibited the proteasome in mid-nanomolar concentrations (IC50 ranging from 57 to 197 nM) and it correlated with cellular potency. In a cell based assay involving green fluorescence protein (GFP) fused to a short degron that is rapidly degraded by a proteasome the compounds induced accumulation of GFP, visualised and quantified by live-cell imaging. Levels of polyubiquitinated proteins in U266 cells treated by compound 4m were also analyzed by immunoblotting, revealing a typical high molecular mass smear of ubiquitin conjugates. Finally, apoptotic cell death in treated U266 cells was detected biochemically by measuring the activity of caspases 3 and 7 in lysates and by immunoblotting of caspase 7, its substrate poly(ADP-ribose)polymerase, and Mcl-1, which all together showed changes typical for apoptosis. All these observations were in agreement with expected cellular mechanism of action and confirmed proteasome targeting by prepared O-benzyl salicylamides.
Keywords: vztahy mezi strukturou a aktivitou; Inhibitor; Salicylamide; salicylamidy; Cell Proliferation; Humans; Structure-Activity Relationship; Molecular Structure; leucin; Antineoplastic Agents; nádorové buněčné linie; Salicylamides; protinádorové látky; Leucine; Drug Screening Assays, Antitumor; fenylalanin; screeningové testy protinádorových léčiv; proliferace buněk; Proteasome Endopeptidase Complex; Ubiquitin; Phenylalanine; proteasomový endopeptidasový komplex; inhibitory proteasomu; Dose-Response Relationship, Drug; Proteasome; vztah mezi dávkou a účinkem léčiva; lidé; Proteasome Inhibitors; Cell Line, Tumor; Apoptosis; molekulární struktura